Intersemiotic translation of contracts into digital environments - Loddo, Olimpia Giuliana; Addis, Andrea; Lorini, Giuseppe (Frontiers in Artificial Intelligence, 2022)
One of the most widespread examples of intersemiotic translation in the contemporary world is transposing natural language into machine language in digital environments. In this case, if the source text is a legal text, we encounter a particular type of intersemiotic translation, namely an intersemiotic legal translation in a digital environment. This paper will focus on the intersemiotic legal translation of contracts in digital environments, and is divided into two parts. In the first part, we will analyze four possible uses of the intersemiotic translation of contracts in a digital context. In particular, we will highlight the technical characteristics of intersemiotic translation, its limitations, and its potential in different phases of contract management, namely the drafting of the document, the agreement, the archiving of the document, and the execution of contractual clauses. We will examine different digital tools that exploit intersemiotic translation, such as contract drafting tools and online platforms that allow for the conclusion of electronic contracts, document archiving in blockchains, and building smart contracts. When analyzing these uses of intersemiotic translation in the digital environment, we will highlight four types of output that can represent the product of intersemiotic translation in the digital environment: epistemic effects, legal effects, digital effects, and economic effects. In the second part, we will describe a hypothetical prototype that, in light of the four potential uses of intersemiotic translation, could represent a support tool to simplify the communication between professional lawyers and clients through the drafting of legal documents with the aid of dynamic forms and, eventually, with the help of artificial intelligence (AI). Beyond facilitating the dialogue between legal professionals and their clients, we use interfaces to allow clients to create their own drafts of their documents and the lawyer to work on the drafts drawn up by the customer, correct them, and structure them in order to guarantee the validity of the document. The system can also be designed to archive legal documents and private deeds securely and entrust them to a professional by using blockchain technology and automating the execution of some contractual clauses via smart contract protocols.